DEVELOPING CRITICAL THINKING SKILLS IN STUDENTS THROUGH BIOLOGICAL PROBLEM MODELING TECHNOLOGIES IN MEDICAL EDUCATION - Atakhanov Sanjarbek Anvarovich; Obidjonova Nilufar Khursandjon Qizi (Bright Mind Publishing, 2025)
This article explores the significance of utilizing biological problem modeling technologies in fostering critical thinking skills among students in medical education. It highlights the integration of modeling technologies into medical and biological sciences and their impact on the educational process. Additionally, the article presents practical examples, discusses relevant software platforms, and outlines future prospects for development in this area.
Keywords: Medical education, critical thinking, modeling, biological problems, information technologies, digital platforms, interactive methods, practical skills.